Factors affecting Consumer Purchase Behavior in online shopping website - Ronald Hasiholan Marbun (Universitas Trisakti, 2007)
The background of this research was to describe how important information features of the website affecting consumers in making purchase commitment in an online shopping. Consumer basically judges their products or service information based on information presented on the site. When consumers are satisfied and happy, we can expec them to be more committed to the site and make repetitive purchase. The objective (s) of this research is to investigate the relationship between information satisfaction and relational benefit to site commitment and purchase behavior in an online shopping website. The hypothesis test uses correlation analysis on relationship between information satisfaction with site commitment and site commitment with purchase behavior. The Moment Pearson test used in this thesis was to find out how strong the relationship of all variables related to site commitment and purchase behavior. The resultsof this research conclude that there are positive relationship about information satisfaction and relational benefit to purchase behavior.